2010
DOI: 10.1080/17441690902756062
|View full text |Cite
|
Sign up to set email alerts
|

Does social status predict adult smoking and obesity? Results from the 2000 Mexican National Health Survey

Abstract: Socioeconomic status is generally associated with better health, but recent evidence suggests that this ‘social gradient’ in health is far from universal. This study examines whether social gradients in smoking and obesity in Mexico—a country in the midst of rapid socioeconomic change—conform to or diverge from results for richer countries. Using a nationally-representative sample of 39 129 Mexican adults, we calculate the odds of smoking and of being obese by educational attainment and by household wealth. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 25 publications
4
39
2
1
Order By: Relevance
“…On the basis of data from economically developing countries (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) , we hypothesized that children from a…”
Section: Snacks Traditional Diet Food Patterns Nutrition Transitionmentioning
confidence: 99%
“…On the basis of data from economically developing countries (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) , we hypothesized that children from a…”
Section: Snacks Traditional Diet Food Patterns Nutrition Transitionmentioning
confidence: 99%
“…7 Socially disadvantaged populations were disproportionately affected and suffered from 8 undernutrition. They were 'protected' from obesity by a lack of material resources and access to 9 calories. As countries develop and economies become largely based on service industries, most 10 can afford high-calorie foods and avoid physical labour.…”
mentioning
confidence: 99%
“…Research regarding the SEP-obesity relationship based on gender differences indicates mixed results. Some studies find a positive SEP-obesity relationship for men and women [7]; while other research finds that men in middle and high SEP categories have increased odds of being obese compared to men in low SEP categories, but the same is not observed for women [8,19]. Research looking at women only finds that obesity prevalence has increased across all SEP groups, measured by living conditions, from 1998 to 2006, but the largest increases have occurred among women in the poorest living conditions [6].…”
Section: Socioeconomic Position and Obesity In Mexicomentioning
confidence: 89%
“…Furthermore the mechanisms by which SEP influences obesity status based on rural and urban residence and gender remain less clear, although research has shown that the SEPobesity relationship in Mexico is nonlinear based on rural or urban residence and gender [19]. Pathways most often mentioned in the literature linking SEP to health status more broadly include local environmental conditions of residential location, household and work settings, coping mechanism to deal with stress, health behaviors (including diet and nutrition) and knowledge, and access to appropriate health care [5,24,25].…”
Section: Socioeconomic Position and Obesity In Mexicomentioning
confidence: 99%
See 1 more Smart Citation